The witch of Blackbird Pond - Speare, Elizabeth George (Houghton Mifflin, 1958)
In 1687 in Connecticut, Kit Tyler, feeling out of place in the Puritan household of her aunt, befriends an old woman considered a witch by the community and suddenly finds herself standing trial for witchcraft.